Emergence of corn according to the sowing depth of the seed and loads on press wheels - Neto,Pedro H. Weirich (2012)
The seeding process was the operation that suffered the most changes in no-tillage system due the cover crop soil and new particle soil arrangement. The objective of this study was to verify the effects of loads applied to the wheels and adjustments of sowing depth on seedling emergence of corn in no-tillage system. The experimental design was completely randomized with a factorial arrangement 5x4, with five loads applied to the wheels and four theoretical sowing depth adjustments. The real sowing depth increased in the lower theoretical depth and decreased in the higher theoretical depth, due to the compaction loads. Regarding the time of emergence, loads applied had not influence at the greater depths. Emergence time decreased with the load increase in the lower depths. Thus, the adjustment of the compactor wheels can influence in the corn seeding process.